Identifying cultural landscape components in the district of Kuala Kangsar, Perak, Malaysia - Mansor, Mazlina; Abdul Latip, Nurul Syala; Salleh, Nurul Hamiruddin; Kamaruddin, Zumahiran; Mahamod, Lukman Hakim (2013)
The paper aims to identify the components that exist in the cultural landscapes of the Kuala Kangsar district, Malaysia. This paper presents a part of a larger study from four disciplines in the built environment, which explore and evaluate the values of heritage components of a district in Malaysia. The aim is to characterize a ‘heritage district’ in Malaysian towns. Therefore, for landscape architecture discipline, the paper reviews the types of the cultural landscape component and explain them in relation to the case study site, i.e. Kuala Kangsar, a district in Perak, Peninsular Malaysia. Kuala Kangsar is a district with many historical legacies and diverse natural, tangible and intangible cultural landscapes. These include rivers, traditional Malay villages, royal town with its historic buildings, open spaces and landscape structures, and traditions which date as far back to the Malacca Sultanate era (15th century). The components are the results of the activities of the local people and their interactions with a place.